Trends in Childhood Leukemia in Basrah, Iraq, 1993–2007 - Hagopian, Amy (American Public Health Association, 2010)
Objectives. Through a sister-university relationship between the University of Basrah and the University of Washington, we analyzed Ibn Ghazwan Hospital's leukemia registry data to evaluate trends in childhood leukemia since 1993. Methods. We documented leukemia cases among children aged 0 to 14 years for each of the last 15 years. Population data were obtained from a 1997 census and various subsequent estimates to calculate rates. Results. We observed 698 cases of childhood leukemia between 1993 and 2007, ranging between 15 cases (2.6 per 100 000 annual rate) in the first year and 56 cases (6.9 per 100 000 annual rate) in the final year, reaching a peak of 97 cases in 2006 (12.2 per 100 000 annual rate). Conclusions. Childhood leukemia rates in Basrah more than doubled over a 15-year period. The test for trend was significant (P = .03). Basrah's childhood leukemia rate compared unfavorably with neighboring Kuwait and nearby Oman, as well as the United States, the European Union, and other countries.